... in the darkest night that is ... Briggs, Blundeville, Wright, and the misconception of finding latitude. Issue 1 (2nd January 2017) - Sonar, Thomas
Abstract : Dedicated to the memory of Jacqueline Stedall When William Gilbert published his monumental work De magnete in 1600 natural philosophy in early modern England was born. In his work Gilbert included a theory of magnetic inclination, called dip, and devised an instrument to find latitude from dip. Here we describe and analyse this theory which was turned into mathematics by Henry Briggs.